Rubber composition and pneumatic tire
Patent Information
- Application Number
- JP2021567442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-21
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-12-21
AI Technical Summary
【0021】 本発明は、陽イオン性官能基及び/又は陰イオン性官能基を含む官能基を有するゴム成分と、前記官能基と対となる電荷を発生させるフィラー、硫黄とを含有するゴム組成物であるので、自己修復性を有する結合を有するゴム組成物において、優れた強度及びウェットグリップ性能が得られる。
Smart Images

Figure 0007635722000001 
Figure 0007635722000002 
Figure 0007635722000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition and a pneumatic tire. [Background technology]
[0002] Rubber with self-repairing properties has been attracting attention as a way to extend the life of rubber, and various studies are being conducted (for example, see Non-Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Non-Patent Document 1] Aladdin Sallat, et al., “Viscoelastic and self-healing behavior of silica filled ionically modified poly(isobutylene-co-isoprene) rubber”, RSCAdvances, 2018, 8, 26793-26803 Summary of the Invention [Problem to be solved by the invention]
[0004] As a result of the inventor's investigations, it was found that rubber having self-repairing properties can provide good strength and wet grip performance, but further investigations revealed that there is room for further improvement.
[0005] An object of the present invention is to solve the above problems and to provide a rubber composition that improves strength and wet grip performance in a rubber having self-repairing properties, and a pneumatic tire using the same. [Means for solving the problem]
[0006] In rubber, it is necessary to bond between molecular chains in order to develop strength according to the mode of use, but if an input exceeding the strength of the bonds between molecular chains occurs, the bonds will be broken, and it is thought that the strength of the entire rubber will decrease as it is continuously deformed. Therefore, the present inventors have investigated a rubber composition with self-repairing properties that can suppress the decrease in strength due to repeated deformation of the rubber by forming reversible bonds such as metal coordinate bonds, hydrogen bonds, and ionic bonds by combining a rubber (polymer) having cationic functional groups and / or anionic functional groups with a filler that generates a counter charge.
[0007] On the other hand, the reversible bond has a self-repairing function and has a certain strength in the matrix, but is inferior to a covalent bond in terms of strength. As a result of further investigation, the present inventors found that adding sulfur to a composition containing the above-mentioned polymer and filler significantly improves the strength and wet grip performance in a rubber composition having a self-repairing bond, and arrived at the present invention. That is, the present invention relates to a rubber composition containing a rubber component having a functional group including a cationic functional group and / or an anionic functional group, a filler that generates an electric charge paired with the functional group, and sulfur.
[0008] The functional group preferably includes a cationic functional group and an anionic functional group.
[0009] It is preferred that the filler contains cationic and / or anionic functional groups.
[0010] The rubber component is preferably at least one selected from the group consisting of butyl rubber, styrene-butadiene rubber, and butadiene rubber.
[0011] The filler is preferably at least one selected from the group consisting of silica and carbon black.
[0012] It is preferable that the cationic functional group contains at least one selected from the group consisting of a pyridine group, an imidazole group, a thiazole group, and an amino group, and the anionic functional group contains at least one selected from the group consisting of a halogen group and a carboxylic acid group.
[0013] It is preferable that the cationic functional group contains an imidazole group, and the anionic functional group contains a halogen group.
[0014] It is preferable that the content of the cationic functional group in the rubber component is 0.5 to 30% by mass, and the content of the anionic functional group in the filler is 5 to 70% by mass.
[0015] It is preferable that the content of anionic functional groups in the rubber component is 0.5 to 30% by mass, and the content of cationic functional groups in the filler is 10 to 70% by mass.
[0016] The amount of the sulfur is preferably 0.3 to 6 parts by mass based on 100 parts by mass of the rubber component.
[0017] It is preferable that the rubber component contains at least one selected from the group consisting of butyl rubber having a 1-butylimidazole group and a bromo group, butyl rubber having a bromo group, styrene-butadiene rubber having a carboxylic acid group, and amine-group styrene-butadiene rubber, and that the filler contains at least one selected from the group consisting of silica having a hydroxyl group, silica having a 1-butylimidazole group and a bromo group, silica having a bromo group, and silica having an amino group.
[0018] The rubber composition preferably satisfies the following formula: Filler content / sulfur content Quantity ≦ 40
[0019] The rubber composition is preferably used in the tread of a tire.
[0020] The present invention also relates to a pneumatic tire having a tread using the above rubber composition. Effect of the Invention
[0021] The present invention relates to a rubber composition containing a rubber component having a functional group including a cationic functional group and / or an anionic functional group, a filler that generates an electric charge that pairs with the functional group, and sulfur, and therefore, in a rubber composition having bonds with self-repairing properties, excellent strength and wet grip performance can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention relates to a rubber composition comprising a rubber component having a functional group including a cationic functional group and / or an anionic functional group, a filler that generates an electric charge that pairs with the functional group in the rubber component, and sulfur.
[0023] In the above rubber composition, reversible bonds are formed by the charge generated by the functional group in the rubber component and the opposing charge generated in the filler, and covalent bonds are also formed by sulfur crosslinking. This creates strong bonds between the polymers through covalent bonds, and also creates reversible bonds between the polymer and filler. As a result, when the rubber component deforms, the reversible bonds, which are weak bonds, are selectively cleaved, absorbing the energy of deformation and allowing the covalent bonds to ensure sufficient strength, which is presumably significantly improving the strength of the entire rubber composition.
[0024] In addition, in the above rubber composition, the bonds between the polymer and filler are formed to a certain extent during kneading, and the polymers are constrained while maintaining a distance between them, so it is believed that in the subsequent sulfur crosslinking, polysulfide bonds are more likely to be formed than monosulfide bonds. This increases the mobility of the polymer molecules, and when the rubber is deformed, the reversible bonds are cleaved, making it easier for energy loss to occur, which is presumably why wet grip performance is significantly improved.
[0025] The functional group in the rubber component includes a cationic functional group and / or an anionic functional group, and the filler generates a counter charge. For example, when the functional group of the rubber component includes a cationic functional group, the filler is required to generate at least a negative charge, and when the functional group of the rubber component includes an anionic functional group, the filler is required to generate at least a positive charge. When the functional group of the rubber component includes a cationic functional group and an anionic functional group, the filler may generate only a positive charge, only a negative charge, or both a positive charge and a negative charge.
[0026] Examples of cationic functional groups include basic functional groups. Examples of basic functional groups include amino groups, imino groups (=NH), ammonium bases, and heterocyclic groups having a basic nitrogen atom. Examples of amino groups include primary amino groups (-NH2), secondary amino groups (-NHR 1 ), tertiary amino group (-NR 1 R 2 ) may be any of the above. 1 and R 2 is an alkyl group, a phenyl group, an aralkyl group, etc., and preferably has 1 to 8 carbon atoms. Examples of the ammonium base include a tertiary ammonium base and a quaternary ammonium base. Examples of the heterocyclic group having a basic nitrogen atom include nitrogen-containing heterocyclic groups such as a pyridine group, a pyrimidine group, a pyrazine group, an imidazole group, an imidazole group containing a thiol, a triazole group, and a thiazole group. In the case of a heterocyclic group, the presence of a double bond makes it easy to disperse in the rubber. Among these, from the viewpoint of easy interaction with the filler and easy obtaining of good strength, a pyridine group, an imidazole group, a thiazole group, and an amino group (amine group) are preferred, and an imidazole group is more preferred.
[0027] Examples of the anionic functional group include a halogen group and an acidic functional group. Examples of the halogen group include a fluoro group, a chloro group, a bromo group, and an iodine group. Examples of the acidic functional group include a hydroxyl group, a carboxylic acid group, a sulfonic acid group, a sulfuric acid group, a phosphonic acid group, a phosphoric acid group, a phosphinic acid group, a maleic acid group, an acid anhydride group (maleic anhydride group, etc.), a fumaric acid group, an itaconic acid group, an acrylic acid group, a methacrylic acid group, and a mercapto group. Among these, from the viewpoint of self-repair function, a halogen group and a carboxylic acid group are preferred, and a halogen group (particularly a bromo group) is more preferred.
[0028] The functional group may include a cationic functional group and an anionic functional group. That is, the functional group may be an amphoteric (zwitterionic) functional group. When all of the functional groups are zwitterionic functional groups, it is presumed that an ionic bond is generated between the positive charge in the functional group and the negative charge in the filler by kneading, and an ionic bond is generated between the negative charge in the functional group and the positive charge in the filler. Examples of such a form include an ionic bond between a nitrogen-containing heterocyclic group (cationic functional group) such as a thiazole group and a halogen group (anionic functional group), and the like, and a group represented by the following formula is preferred. [ka] (In the formula, X is Br or Cl (preferably Br), and R is an alkyl group having 1 to 10 carbon atoms (preferably 1 to 4 carbon atoms).)
[0029] In the rubber component, when the functional group contains a cationic functional group, the content of the cationic functional group is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, even more preferably 1.5% by mass or more, and also preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. Within the above ranges, the effect tends to be better obtained. Similarly, when the functional group contains an anionic functional group, the content of the anionic functional group is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, even more preferably 1.5% by mass or more, and also preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0030] In the rubber component, the content of each functional group can be measured by carrying out NMR measurement and calculating the content (mass%) based on the peak corresponding to each functional group.
[0031] The rubber component is not particularly limited, but examples thereof include diene rubbers such as isoprene rubber, butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene butadiene rubber (SIBR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), and acrylonitrile butadiene rubber (NBR), acrylic rubbers such as butyl acrylate rubber, ethyl acrylate rubber, and octyl acrylate rubber, nitrile rubber, isobutylene rubber, methyl methacrylate-butyl acrylate block copolymer, ethylene-propylene copolymer (EPR), chlorosulfonated polyethylene, silicone rubber (millable type, room temperature vulcanization type), butyl rubber, fluororubber, olefin thermoplastic elastomer, styrene thermoplastic elastomer, PVC thermoplastic elastomer, and urethane thermoplastic elastomer. Examples of the thermoplastic elastomer include polyamide-based thermoplastic elastomers, polyester-based thermoplastic elastomers, styrene-isobutylene-styrene block copolymers (SIBS), styrene-isoprene-styrene block copolymers (SIS), styrene-isobutylene block copolymers (SIB), styrene-butadiene-styrene block copolymers (SBS), styrene-ethylene-butene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), and styrene-butadiene-butylene-styrene block copolymers (SBBS). Of these, those that do not have the functional group as the basic skeleton can be obtained by adding a functional group appropriately. These may be used alone or in combination of two or more. Among them, from the viewpoint of tire physical properties, butyl rubber, SBR, and BR are preferred, and butyl rubber is more preferred. In addition, when two or more types are used in combination, it is sufficient that any one of the rubber components has the functional group.
[0032] The butyl rubber, SBR, and BR are not particularly limited, and those generally used in the rubber industry can be used. Commercially available products include those from Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, and the like.
[0033] In 100% by mass of the rubber component, the content of the rubber component having the functional group is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more, and may be 100% by mass. When it is within the above range, the effect tends to be better obtained.
[0034] In 100% by mass of the rubber component, the total content of the butyl rubber, SBR and BR is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more, and may be 100% by mass. When it is within the above range, the effect tends to be better obtained.
[0035] In 100% by mass of the rubber component, the content of the butyl rubber is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more, and may be 100% by mass. When it is within the above range, the effect tends to be better obtained.
[0036] In 100% by mass of the rubber component, the content of the SBR is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more, and may be 100% by mass. When it is within the above range, the effect tends to be better obtained.
[0037] Examples of fillers that generate charges that pair with the functional groups of the rubber component include rubber reinforcing agents such as silica and carbon black; metal oxides such as zinc oxide, magnesium oxide, aluminum oxide, and titanium oxide; hydroxides such as aluminum hydroxide and magnesium hydroxide; alkaline earth metal salts such as calcium carbonate and magnesium sulfate; alkali metal salts such as sodium chloride and potassium chloride; silicate minerals such as smectites such as montmorillonite, bentonite, hectorite, and saponite, sepiolite, vermiculite, chlorite, kaolinite, talc, mica, and clay; and the like. These may be used alone or in combination of two or more. Among these, silica and carbon black are preferred from the viewpoint of tire physical properties, and silica is more preferred.
[0038] In the case of silica and carbon black, the hydroxyl groups present on the surface of the filler act as negative charges, which are believed to form a reversible bond with the rubber component. On the other hand, in the case of metal oxides, the metal ion portion is ionized by the functional groups in the rubber component to generate a positive charge, which is believed to form a reversible bond with the rubber component. In the case of salts, both positive and negative charges are generated when ionization occurs, so it is believed that either one or both of them form a reversible bond with the functional groups of the rubber component.
[0039] In addition, in the above filler, a part of the filler structure may be modified to the cationic functional group and / or anionic functional group to enhance the binding with the functional group in the rubber component. As the filler to be modified in this way, silica and carbon black are preferable from the viewpoint of excellent tire properties.
[0040] In the above filler, when a part of the filler structure is modified to the cationic functional group and / or anionic functional group, the content of the cationic functional group is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and also preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. Within the above range, the effect tends to be better obtained. Similarly, when the filler contains an anionic functional group, the content of the anionic functional group is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, particularly preferably 20% by mass or more, and also preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. In addition, in the above filler, the content of each functional group can be measured by carrying out TGA measurement and calculating from the weight (mass) reduction rate.
[0041] The silica and carbon black are not particularly limited, and those generally used in the rubber industry can be used. Commercially available silica products include those from EVONIK, Tosoh Silica Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Co., Ltd., etc., and commercially available carbon black products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shin-Nichika Carbon Co., Ltd., Columbia Carbon Co., Ltd., etc.
[0042] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 100 m 2 / g or more, more preferably 150m 2 / g or more, more preferably 180m 2 / g or more, and preferably 250m 2 / g or less, more preferably 220m 2 / g or less, more preferably 200m 2 / g or less. When the N2SA is within the above range, it is considered that the interaction with the polymer is easily generated and at the same time, the ionic bond is easily formed, and the above-mentioned effect tends to be obtained well. The nitrogen adsorption specific surface area of silica is a value measured by the BET method according to ASTM D3037-81.
[0043] The content of the filler is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more, relative to 100 parts by mass of the rubber component, and is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 45 parts by mass or less. By making the content equal to or more than the lower limit, a good reinforcing effect due to ionic bonds tends to be obtained, while by making the content equal to or less than the upper limit, a filler that forms well with ionic bonds is easily generated, and the above effect tends to be obtained well.
[0044] Silica may be used in combination with a silane coupling agent. The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-triethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamate, Examples of such silanes include sulfide-based silanes such as bamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based silanes such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and Momentive's NXT and NXT-Z; vinyl-based silanes such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based silanes such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy-based silanes such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silanes such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based silanes such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Commercially available products include those from EVONIK, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industry, Azumax, and Dow Corning Toray Co., Ltd. These may be used alone or in combination of two or more.
[0045] The content of the silane coupling agent is preferably 3 parts by mass or more, more preferably 6 parts by mass or more, and also preferably 12 parts by mass or less, more preferably 8 parts by mass or less, based on 100 parts by mass of silica. By making it equal to or more than the lower limit, the silica is prevented from being hydrophobized due to the hydrophobic skeleton of the rubber, and dispersion is improved, and excellent strength tends to be obtained. By making it equal to or less than the upper limit, it is believed that the hydroxyl group on the silica surface is prevented from reacting with the silane coupling agent, and ionic bonds are formed well.
[0046] The rubber composition contains sulfur. Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. Commercially available products include those from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. These may be used alone or in combination of two or more kinds.
[0047] The content of sulfur is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, and is preferably 6 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, a network by sulfur is sufficiently formed, and good strength tends to be obtained. By making it equal to or less than the upper limit, the covalent bond network is prevented from becoming too strong, and good polymer mobility tends to be obtained. In addition, since it is considered that the formation of the network by sulfur is also involved in the sulfur element contained in the vulcanization accelerator, in addition to the powdered sulfur contained as a vulcanizing agent, if a vulcanization accelerator is contained, the sulfur content referred to here refers to the net amount of sulfur element in the rubber component.
[0048] The net amount of sulfur can be calculated by an oxygen combustion flask method in accordance with JIS-K6233:2016, and the amount of sulfur dioxide generated after oxygen combustion may be quantified by infrared absorption spectroscopy.
[0049] The rubber composition may contain a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazylsulfenamide (CBS), N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-oxyethylene-2-benzothiazolesulfenamide, and N,N'-diisopropyl-2-benzothiazolesulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolylguanidine, and orthotolylbiguanidine. Commercially available products include products from Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and the like. These may be used alone or in combination of two or more kinds.
[0050] The content of the vulcanization accelerator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 4 parts by mass or less, more preferably 2 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above range, the effect tends to be better.
[0051] The rubber composition may contain zinc oxide. As the zinc oxide, a conventionally known one can be used, and as a commercially available product, a product from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc. can be used. These may be used alone or in combination of two or more. In the present invention, as known from the prior art, zinc oxide is considered to be capable of activating the vulcanization reaction of rubber and at the same time forming a reversible bond with the functional group of the rubber component.
[0052] The amount of zinc oxide is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, and even more preferably 1 part by mass or more, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, based on 100 parts by mass of the rubber component. When the amount is within the above range, the effect tends to be better obtained.
[0053] The rubber composition may contain a plasticizer. The plasticizer is a material that imparts plasticity to the rubber component and a component that is extracted with acetone, and examples of the plasticizer include liquid plasticizers (plasticizers that are in a liquid state at room temperature (25° C.)) and resins (resins that are in a solid state at room temperature (25° C.)).
[0054] The liquid plasticizer includes oil. Examples of the oil include process oil, vegetable oil, and mixtures thereof. Examples of the process oil include paraffin-based process oil, aromatic process oil, and naphthenic process oil. Examples of the vegetable oil include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil. Examples of commercially available products include products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., JXTG Nippon Oil & Energy Corporation, Orisoi Co., Ltd., H&R Co., Ltd., Toyokuni Oil Mill Co., Ltd., Showa Shell Sekiyu K.K., Fuji Kosan Co., Ltd., and the like. These may be used alone or in combination of two or more.
[0055] The content of the oil is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, and is preferably 40 parts by mass or less, and more preferably 30 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above range, the effect tends to be better obtained.
[0056] The resin may be an adhesive resin. Examples of adhesive resins include aromatic hydrocarbon resins commonly used in the tire industry, such as phenolic resins, alkylphenolic resins, terpene resins, coumarone resins, indene resins, coumarone-indene resins, styrene resins, acrylic resins, rosin resins, and dicyclopentadiene resins (DCPD resins), aliphatic hydrocarbon resins such as C5 resins, C8 resins, C9 resins, and C5 / C9 resins, and hydrogenated products thereof. Commercially available products include those from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Co., Ltd., Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., JXTG Energy Corporation, Nippon Zeon Co., Ltd., Harima Chemical Co., Ltd., Toagosei Co., Ltd., Arakawa Chemical Co., Ltd., and Taoka Chemical Co., Ltd. These may be used alone or in combination of two or more kinds.
[0057] The content of the adhesive resin is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, based on 100 parts by mass of the rubber component. When the content is within the above range, the effect tends to be better.
[0058] The rubber composition may contain a wax. The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as vegetable wax and animal wax; and synthetic waxes such as polymers of ethylene, propylene, etc. Commercially available products include those from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Seiko Chemical Co., Ltd., etc. These may be used alone or in combination of two or more kinds.
[0059] The amount of the wax is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above range, the effect tends to be better obtained.
[0060] The rubber composition may contain an antioxidant. Examples of the antioxidant include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine. Examples of the antioxidant include p-phenylenediamine antioxidants such as quinolinone; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. Commercially available products include those from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and Flexis Co., Ltd. These may be used alone or in combination of two or more.
[0061] The content of the antioxidant is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and is preferably 6 parts by mass or less, more preferably 3 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above range, the effect tends to be better.
[0062] The rubber composition may contain stearic acid. As the stearic acid, a conventionally known one can be used, and as a commercially available product, a product from NOF Corp., Kao Corp., Fujifilm Wako Pure Chemical Corp., Chiba Fatty Acid Corp., etc. can be used. These may be used alone or in combination of two or more kinds.
[0063] The content of stearic acid is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the rubber component. When the content is within the above range, the effect tends to be better obtained.
[0064] In addition to the above components, the rubber composition may further contain additives commonly used in the rubber industry, such as organic peroxides, etc. The content of these additives is preferably 0.1 to 200 parts by mass per 100 parts by mass of the rubber component.
[0065] From the viewpoint of obtaining the desired effect, it is preferable that the content (parts by mass) of the filler per 100 parts by mass of the rubber component and the content (parts by mass) of the sulfur per 100 parts by mass of the rubber component satisfy the following formula: Filler content / sulfur content Quantity ≦ 40
[0066] The upper limit of the filler content / sulfur content is preferably 35 or less, more preferably 25 or less. The lower limit is not particularly limited, but is preferably 10 or more, more preferably 15 or more. By keeping it within the above range, it is believed that self-repairing bonds and covalent bonds by sulfur are easily formed at the same time, and the sulfur bonds are also promoted to become poly-crosslinked, resulting in good wet grip performance and strength.
[0067] The rubber composition can be produced, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll or a Banbury mixer, and then vulcanizing the mixture.
[0068] As for the kneading conditions, in the base kneading step in which additives other than sulfur and the vulcanization accelerator are kneaded, the kneading temperature is usually 100 to 180°C, preferably 120 to 170°C. In the finish kneading step in which sulfur and the vulcanization accelerator are kneaded, the kneading temperature is usually 120°C or lower, preferably 85 to 110°C. Furthermore, the composition kneaded with sulfur and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is usually 140 to 190°C, preferably 150 to 185°C. The vulcanization time is usually 5 to 15 minutes.
[0069] The rubber composition can be suitably used, for example, in a tire tread (cap tread).
[0070] The pneumatic tire of the present invention is produced by a conventional method using the above rubber composition. That is, the rubber composition is extruded in an unvulcanized state to match the shape of the tread, and molded together with other tire components in a tire building machine by a normal method to form an unvulcanized tire. The unvulcanized tire is then heated and pressurized in a vulcanizer to obtain a tire.
[0071] The pneumatic tire can be used as a passenger car tire, a heavy load tire for trucks, buses, etc., a light truck tire, a two-wheeled vehicle tire, a racing tire (high performance tire), etc. It can also be used as an all-season tire, a summer tire, a studless tire (winter tire), etc.
[0072] Passenger car tires are tires that are installed on automobiles that are designed for four-wheel drive and have a standard load capacity of 1,000 kg or less.
[0073] Here, the "normal load" refers to the load that is determined for each tire by each standard in the standard system including the standard on which the tire is based. In the case of JATMA, it is the "maximum load capacity." In the case of TRA, it is the maximum value listed in the table "TIRE LOAD LIMITS AT VARIOUS COLD INFLATION PRESSURES." In the case of ETRTO, it is the "LOAD CAPACITY." EXAMPLES
[0074] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.
[0075] The various chemicals used in the examples and comparative examples will be described below.
[0076] Rubber 1: Production Example 1 below (butyl rubber having a cationic functional group (1-butylimidazole group) and an anionic functional group (bromo group), cationic functional group: 1.0 mass%, anionic functional group: 1.0 mass%) Rubber 2: BROMOBUTYL 2255 manufactured by ExxonMobil Chemical (butyl rubber having an anionic functional group (bromo group), anionic functional group: 1.0% by mass) Rubber 3: Latex manufactured by Zeon Corporation (SBR having an anionic functional group (carboxylic acid group), anionic functional group: 30% by mass) Rubber 4: Production Example 2 below (SBR having a cationic functional group (amine group), cationic functional group: 30% by mass) Filler 1: ULTRASIL VN3 manufactured by EVONIK (silica having anionic functional groups (hydroxyl groups), anionic functional groups: 5% by mass, N2SA: 180m 2 / g) Filler 2: Production Example 3 below (silica having a cationic functional group (1-butylimidazole group) and an anionic functional group (bromo group), cationic functional group: 10% by mass, anionic functional group: 10% by mass) Filler 3: Production Example 4 below (silica having an anionic functional group (bromo group), anionic functional group: 10% by mass) Filler 4: Production Example 5 below (silica having a cationic functional group (amino group), cationic functional group: 10% by mass) Filler 5: Clay Hard clay crown manufactured by Southeastern Clay Company (average particle size: 0.6 μm) Filler 6: Aluminum hydroxide APYRAL200SM (average particle size: 0.6 μm) manufactured by Nabaltec Filler 7: Carbon black, Cabot Japan Co., Ltd.'s Show Black N220 (N2SA: 114m 2 / g) Filler 8: Calcium carbonate Shiraishi Kogyo Co., Ltd.'s Hakuenka CC (average particle size: 1 μm) Filler 9: Magnesium oxide Kyowamag 150 manufactured by Kyowa Chemical Industry Co., Ltd. Zinc oxide: Two types of zinc oxide manufactured by Mitsui Mining & Smelting Co., Ltd. Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Vulcanization accelerator: Noccela NS (N-tert-butyl-2-benzothiazylsulfenamide (TBBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0077] <Production Example 1> Using a 1.7 L Banbury mixer manufactured by Kobe Steel, Ltd., 100 parts by mass of bromobutyl rubber (rubber 2) and 3 parts by mass of 1-butylimidazole were kneaded at 130° C. for 3 minutes to obtain rubber 1.
[0078] <Production Example 2> Into a heat-resistant container that had been thoroughly substituted with nitrogen, 1500 ml of n-hexane, 100 mmol of styrene, 800 mmol of 1,3-butadiene, 5 mmol of p-methoxystyrene, 0.2 mmol of tetramethylethylenediamine, 0.12 mmol of dimethylamine (modifier), and 0.12 mmol of n-butyllithium were added and stirred at 0° C. for 48 hours. After that, alcohol was added to stop the reaction, and 1 g of 2,6-tert-butyl-p-cresol was added to the reaction solution, followed by reprecipitation purification to obtain rubber 4.
[0079] <Production Example 3> In a dried flask, 40 ml of 3-bromopropyltrimethoxysilane and 20 ml of 1-imidazole were stirred at room temperature for 5 days to give 1-butyl-3-trimethoxysilylpropylimidazolium bromide. Next, 120 g of silica (filler 1) and 700 ml of toluene were added to a flask equipped with a reflux condenser, and excess 1-butyl-3-trimethoxysilylpropylimidazolium bromide was added while stirring, and the mixture was heated to reflux at 120° C. for 24 hours. Then, the methanol produced by the reaction was removed, and the mixture was cooled. The silica particles were then collected by centrifugation, thoroughly washed with methanol, and then dried at 110° C. for 12 h to obtain Filler 2.
[0080] <Production Example 4> In a flask equipped with a reflux condenser, 40 g of silica (filler 1) and 700 ml of toluene were added, and while stirring, excess 3-bromopropyltrimethoxysilane was added, and the mixture was heated to reflux at 120° C. for 24 hours. Then, the methanol produced in the reaction was removed, and the mixture was cooled. The silica particles were then collected by centrifugation, thoroughly washed with methanol, and then dried at 110° C. for 12 h to obtain Filler 3.
[0081] <Production Example 5> In a flask equipped with a reflux condenser, 40 g of silica (filler 1) and 700 ml of toluene were added, and while stirring, excess [3-(N,N-dimethylamino)propyl]trimethoxysilane was added, and the mixture was heated to reflux at 120° C. for 24 hours. After removing the methanol produced by the reaction, the mixture was cooled. The silica particles were then collected by centrifugation, thoroughly washed with methanol, and then dried at 110° C. for 12 h to obtain Filler 4.
[0082] <Examples and Comparative Examples> According to the formulations shown in each table, materials other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition (elastomer composition). The resulting unvulcanized rubber composition was press-vulcanized in a 2 mm thick mold at 170° C. for 10 minutes to obtain a vulcanized rubber composition.
[0083] The vulcanized rubber composition was used to carry out the following evaluations. The results are shown in Tables 1 to 4. In the following evaluations, the reference examples are Table 1: Comparative Example A1, Table 2: Comparative Example B1, Table 3: Comparative Example C1, and Table 4: Comparative Example D1. Regarding "filler content / sulfur content" in Tables 1 to 4, the sulfur content (mass%) in the test piece (vulcanized rubber composition) was calculated by the oxygen combustion flask method in accordance with JIS-K6233:2016.
[0084] (strength index) According to JIS K 6251 "Vulcanized rubber and thermoplastic rubber - Determination of tensile properties", a tensile test was carried out using a No. 5 dumbbell made of the above vulcanized rubber composition, and the tensile strength at break (TB) was measured. The TB of the reference example was set to 100, and the TB of each compound was expressed as an index. The larger the index, the larger the TB and the better the strength.
[0085] (Wet grip performance index) Using a viscoelasticity spectrometer VES manufactured by Iwamoto Seisakusho Co., Ltd., the tan δ of the vulcanized rubber composition was measured under the conditions of a measurement temperature of 0°C, an initial strain of 10%, a dynamic strain of 2.5%, and a frequency of 10 Hz, and expressed as an index with the reference example being 100. A larger index indicates a larger tan δ at 0°C and better wet grip performance.
[0086] [Table 1]
[0087] [Table 2]
[0088] [Table 3]
[0089] [Table 4]
[0090] As can be seen from Tables 1 to 4, the examples containing a rubber component having a functional group including a cationic functional group and / or an anionic functional group, a filler that generates an electric charge paired with the functional group, and sulfur exhibited excellent strength and wet grip performance.
Claims
1. The rubber composition includes a rubber component having a functional group including a cationic functional group and / or an anionic functional group, a filler that generates an electric charge paired with the functional group, and sulfur, the functional group comprises a cationic functional group and an anionic functional group; A rubber composition that satisfies the following formula: Filler content / sulfur content≦40
2. The rubber composition includes a rubber component having an imidazole group and a halogen group, a filler that generates an electric charge paired with at least one selected from the group consisting of the imidazole group and the halogen group, and sulfur, The rubber composition, wherein the rubber component is at least one selected from the group consisting of butyl rubber, styrene-butadiene rubber, and butadiene rubber.
3. 2. The rubber composition according to claim 1, wherein the filler contains a cationic functional group and / or an anionic functional group.
4. 2. The rubber composition according to claim 1, wherein the rubber component is at least one rubber selected from the group consisting of butyl rubber, styrene-butadiene rubber, and butadiene rubber.
5. 5. The rubber composition according to claim 1, wherein the filler is at least one selected from the group consisting of silica and carbon black.
6. The rubber composition according to claim 1, wherein the cationic functional group includes at least one selected from the group consisting of a pyridine group, an imidazole group, a thiazole group, and an amino group, and the anionic functional group includes at least one selected from the group consisting of a halogen group and a carboxylic acid group.
7. 2. The rubber composition according to claim 1, wherein said cationic functional group comprises an imidazole group and said anionic functional group comprises a halogen group.
8. 2. The rubber composition according to claim 1, wherein the content of the cationic functional group in the rubber component is 0.5 to 30 mass %.
9. 2. The rubber composition according to claim 1, wherein the content of anionic functional groups in the rubber component is 0.5 to 30% by mass.
10. The rubber composition according to any one of claims 1 to 9, wherein the amount of the sulfur is 0.3 to 6 parts by mass based on 100 parts by mass of the rubber component.
11. The rubber composition according to claim 1, wherein the rubber component comprises at least one selected from the group consisting of butyl rubber having a 1-butylimidazole group and a bromo group, butyl rubber having a bromo group, styrene-butadiene rubber having a carboxylic acid group, and amine-group styrene-butadiene rubber, and the filler comprises at least one selected from the group consisting of silica having a hydroxyl group, silica having a 1-butylimidazole group and a bromo group, silica having a bromo group, and silica having an amino group.
12. The rubber composition according to any one of claims 2 to 11, which satisfies the following formula: Filler content / sulfur content≦40
13. The rubber composition according to any one of claims 1 to 12, which is used for a tire tread.
14. A pneumatic tire having a tread using the rubber composition according to any one of claims 1 to 13.
Citation Information
Patent Citations
Self-healing antiskid unvulcanizedrubber material and preparation method thereof
CN107057136A
Treed rubber composition for high speed tire
JP1991031339A
Elastomer compound containing silica filler
JP2004244635A
Modified polymer and rubber composition and tire using the same
JP2006249189A
Tire
JP2010185053A